Performance of single and double layers of metamaterial absorbers at X-band frequency - Osman Ayop, 1984-, author; Mohamad Kamal A. Rahim, supervisor; Noor Azniza Murad; Fakulti Kejuruteraan Elektrik (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2016